Effect of salinity and inorganic nitrogen of soils in phenols compounds and antioxidant capacity of Lycium berlandieri - Farías Tapia, Rubén; Olivas Sánchez, Martha Patricia; Flores Margez, Juan Pedro; Martínez Ruiz, Nina del Rocío; Álvarez Parrilla, Emilio (REVISTA TERRA LATINOAMERICANA, 2019)
Polyphenolic compounds are antioxidants compounds mainly present in plants and its concentrations may differ between the same species located at different growing points, since plants produce these compounds for protection against oxidative stress as a result of environmental factors that could affect them. The aims of present research, were: to determine the proximate composition; the polyphenolic compounds concentration and antioxidant activity in fruits of Lycium berlandieri, collected in the three locations of the municipality of Juárez, Chihuahua (Riveras del Bravo, San Isidro and San Agustín), to evaluate the effect of the inorganic nitrogen, alkalinity and salinity of the soil on the content of total phenolic and flavonoids compounds. The humidity content in the fruits of L. berlandieri ranged between 78.2 to 93.3%; the proximal composition of the fruit in dry weight indicated an ash content from 3.6 to 5.3%, fats from 0.9 to 6.7% protein from 9.0 to 15.4% and 75.2 to 85.7% total carbohydrates. In terms of polyphenolic compounds (in dry weight), fruits from San Agustín showed the highest concentration of these compounds, particularly in total phenols 12 mg EAG (P = 0.002) and 9.02 mg EC in flavonoids (P = 0.001). Results of soil analysis indicated that the soil of San Agustín showed the highest concentration of nitrates (88.51 mg kg-1) and a more saline soil (6.04 dS m-1). Overall, the results obtained allowed to attribute that the differences in concentration of polyphenolic compounds in the fruits of L. berlandieri, are related to the salinity of the soil and availability of nitrates, therefore the soil of San Agustín in Ciudad Juárez, Chihuahua it is optimal for the cultivation of L. berlandieri.